A Cabinet of Philosophical Curiosities : A Collection of Puzzles, Oddities, Riddles, and Dilemmas - Sorensen, Roy A. (London Profile Book, 2016)
A Cabinet of Philosophical Curiosities is a collection of puzzles, paradoxes, riddles, and miscellaneous logic problems. Depending on taste, one can partake of a puzzle, a poem, a proof, or a pun.
Include Illustration
Keywords: Logic -- Philosophy